Salivary gland Cytology, the new and the Old, a Pattern-Based approach - Shuo Niu; Yanjun Hou (Elsevier, 2024)
Salivary gland neoplasms are rare and represent a diverse group of tumors. Fine-needle aspiration is a cost effective approach that has been widely applied in preoperative diagnosis of salivary gland lesions to guide clinical management. The wide diversity of entities, significant morphological overlap and limited cellularity make salivary gland cytology challenging. A cellular and architectural pattern-based approach can help narrow down the differential diagnoses. In the meantime, molecular understanding has resulted in a rapid expansion and redefining of salivary gland neoplasms. Herein, we reviewed salivary gland cytology which focused on four patterns: basaloid, oncocytic/oncocytoid, mucinous/cystic/secretory and spindle, along with updated immunohistochemical and molecular features.